FADS and PPARG2 Single Nucleotide Polymorphisms are Associated with Plasma Lipids in 9-Mo-Old Infants. Issue 5 (3rd May 2019) - Lauritzen, Lotte; Amundsen, Ingvild D; Damsgaard, Camilla T; Lind, Mads V; Schnurr, Theresia M; Hansen, Torben; Michaelsen, Kim F; Vogel, Ulla
ABSTRACT: Background: Dietary intake of polyunsaturated fatty acids (PUFAs), e.g., linoleic acid and n–3 (ω-3) long-chain PUFAs, has been shown in adults to affect plasma cholesterol and triglycerides (TGs), respectively. Little is known about the effects of PUFAs on plasma lipids in early life. Objective: The aim of this study was to explore the associations between plasma concentrations of total, LDL, and HDL cholesterol and TGs in infants and 2 single nucleotide polymorphisms (SNPs) in the fatty acid desaturase genes ( FADS ) oppositely associated with docosahexaenoic acid ( rs1535 and rs174448 ) and potential effect modification by a functional peroxisome proliferator-activated receptor-γ2 gene variant ( PPARG2 Pro12Ala). Methods: In 9-mo-old infants ( n  = 561) from 3 Danish cohorts, we analyzed associations between plasma lipids, erythrocyte PUFAs, and FADS SNPs, and interactions with PPARG2 Pro12Ala genotype, by multiple linear regression. We also examined potential effect modification by breastfeeding, as 46% of the infants were still being breastfed. Results: Minor allele carriage of rs174448 was associated with lower total cholesterol (difference: −0.22 mmol/L; 95% CI: −0.37, −0.06 mmol/L; P  = 0.006) and LDL cholesterol (difference: −0.15 mmol/L; 95% CI: −0.29, −0.01 mmol/L; P  = 0.035), but no associations were observed with TGs or for rs1535 . Minor allele carriage of both FADS SNPs was associated with 1 SD lower HDL cholesterol, but only in currently breastfed infants ( rs174448 ×  breastfeeding, P  = 0.080; rs1535 ×  breastfeeding, P  = 0.030) and PPARG2 minor allele carriers ( rs174448 × PPARG2, P  = 0.001; rs1535 × PPARG2, P  = 0.004). Erythrocyte arachidonic acid and eicosapentaenoic acid were inversely associated with LDL cholesterol [estimated effect (β): −0.3 mmol/L; 95% CI: −0.06, −0.00 mmol/L per percentage of fatty acids (FA%); P  = 0.035] and TGs (β: −0.23 mmol/L; 95% CI: −0.41, −0.05 mmol/L per FA%; P  = 0.015), respectively. Conclusions: The observed associations with FADS variants indicate that PUFAs are involved in plasma lipid regulation in 9-mo-old infants. Observed FADS SNP differences and interactions with breastfeeding and PPARG2 warrant additional studies to explore the effects of individual FADS SNPs on PUFA status and potential genetic modification of dietary PUFA effects.